Optimisation of membrane technology for water reuse - Raffin, Marie (Cranfield University, 2011)
Increasing freshwater scarcity is making reclamation of wastewater effluent more economically attractive as a means of preserving freshwater resources. The use of an integrated membrane system (IMS), the combination of micro/ultra-filtration (MF/UF) followed by reverse osmosis (RO) membranes, represents a key process for municipal wastewater reuse. A major drawback of such systems is the fouling of both the MF/UF and RO membranes. The water to be treated by the IMS system varies from one wastewater treatment plant (WWTP) to another, and its fouling propensity changes correspondingly. It is thus preferable to conduct pilot trials before implementing a full-scale plant. This thesis aims to look at the sustainability of IMS technology dedicated to indirect potable reuse (IPR) in terms of fouling minimisation and cost via a 600 m3 .d- 1 pilot plant. Wastewater reuse plants, using IMS, as well as statistical methods for membrane optimisation were reviewed. Box-Behnken design was used to define optimum operating envelopes of the pilot plant for both the microfiltration and the reverse osmosis in terms of fouling minimisation. Same statistical method was used to enhance the efficiency of the MF cleaning-in place through bench-scale test. Data from the pilot plant MF process allow to determine relationship between reversible and irreversible fouling, and operating parameters and feed water quality. Life cycle cost analysis (LCCA) of the both trains (MF/RO/AOP and MF/AOP) of the pilot plant was performed and compared with the LCCA of two full-scale plant.
Keywords: Integrated membrane system; wastewater reuse; optimisation; Box-Behnken design; operating parameters; fouling; Life cycle cost